THE IMPORTANCE OF USING THE VIRTUAL LABORATORY IN CHEMISTRY EDUCATION - Abduraximova Mo‘tabar Adashboyevna, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
. In recent years, the integration of virtual laboratories into chemistry education has emerged as an advanced approach to teaching. This paper examines the value of virtual laboratories in enhancing the learning experience for chemistry students. Virtual labs have many advantages such as convenience, flexibility, security, visualization, cost effectiveness, time efficiency, technology integration, customization, adaptability, distance learning opportunities, and environmental sustainability. Using advances in technology, virtual labs allow students to conduct experiments, visualize molecular structures, analyze data, and reinforce conceptual understanding in a safe and controlled environment. Through a comprehensive examination of the importance of virtual laboratories, this article highlights their importance in developing students' STEAM-based understanding of chemical processes.